Hepatic changes in the failing Fontan circulation. Issue 5 (27th September 2006) - Kiesewetter, Christoph H; Sheron, Nick; Vettukattill, Joseph J; Hacking, Nigel; Stedman, Brian; Millward-Sadler, Harry; Haw, Marcus; Cope, Richard; Salmon, Anthony P; Sivaprakasam, Muthukumaran C; Kendall, Tim; Keeton, Barry R; et al.
Abstract : Background: The failing Fontan circulation is associated with hepatic impairment. The nature of this liver injury is poorly defined. Objective: To establish the gross and histological liver changes of patients with Fontan circulation relative to clinical, biochemical and haemodynamic findings. Methods: Patients were retrospectively assessed for extracardiac Fontan conversion between September 2003 and June 2005, according to an established clinical protocol. Twelve patients, mean age 24.6 (range 15.8–43.4) years were identified. The mean duration since the initial Fontan procedure was 14.1 (range 6.9–26.4) years. Results: Zonal enhancement of the liver (4/12) on CT was more common in patients with lower hepatic vein pressures (p = 0.007), and in those with absent cardiac cirrhosis on histological examination (p = 0.033). Gastro-oesophageal varices (4/12) were more common in patients with higher hepatic vein pressure (21 (6.3) vs 12.2 (2.2) mm Hg, p = 0.013) and associated with more advanced cirrhosis (p = 0.037). The extent of cirrhosis (7/12) was positively correlated with the hepatic vein pressure (r = 0.83, p = 0.003). A significant positive correlation was found between the Fontan duration and the degree of hepatic fibrosis (r = 0.75, p = 0.013), as well as presence of broad scars (r = 0.71, p = 0.021). Protein-losing enteropathy (5/12) occurred more frequently in patients with longer Fontan duration (11.7 (3.2) vs 17.9 (6.1) years, p = 0.038). Conclusions: Liver injury, which can be extensive in this patient group, is related to Fontan duration and hepatic vein pressures. CT scan assists non-invasive assessment. Cardiac cirrhosis with the risk of developing gastro-oesophageal varices and regenerative liver nodules, a precursor to hepatocellular carcinoma, is common in this patient group.